Electron-induced ligand loss from iron tetracarbonyl methyl acrylate - Lyshchuk, Hlib; Chaudhary, Atul; Luxford, Thomas F M; Ranković, Miloš; Kočišek, Jaroslav; Fedor, Juraj; McElwee-White, Lisa; Nag, Pamir (Beilstein journal of nanotechnology, 2024)
We probe the separation of ligands from iron tetracarbonyl methyl acrylate (Fe(CO)4(C4H6O2) or Fe(CO)4MA) induced by the interaction with free electrons. The motivation comes from the possible use of this molecule as a nanofabrication precursor and from the corresponding need to understand its elementary reactions fundamental to the electron-induced deposition. We utilize two complementary electron collision setups and support the interpretation of data by quantum chemical calculations. This way, both the dissociative ionization and dissociative electron attachment fragmentation channels are characterized. Considerable differences in the degree of precursor fragmentation in these two channels are observed. Interesting differences also appear when this precursor is compared to structurally similar iron pentacarbonyl. The present findings shed light on the recent electron-induced chemistry of Fe(CO)4MA on a surface under ultrahigh vacuum.
Keywords: electron collision; iron tetracarbonyl methyl acrylate; focused electron beam-induced deposition (FEBID); FEBID precursor